Diamond-like Carbon Coatings for Artificial Implant - Rothammer, Benedict; Marian, Max (Applications of Diamond‐like Carbon Coatings, 2025)
This chapter delves into the enhancement of implant performance through diamond-like carbon (DLC) coatings, recognized for their exceptional mechanical, chemical, and biocompatible properties, making them ideal for various biomedical applications. The chapter focuses on orthopedic applications, where DLC coatings improve wear resistance and longevity of implants, and promote osteointegration by enhancing cell adhesion and proliferation. In dental implants, DLC coatings boost biocompatibility and reduce infection risk, while also enhancing the durability of orthodontic brackets. This chapter details the requirements for DLC coatings in artificial implants and reviews their use in load bearing and dental implants, respectively. The chapter concludes with a summary of findings and identifies future research challenges, emphasizing the need for translating model-level advancements to component-level applications and addressing the reproducibility issues in dental applications. Overall, DLC coatings show significant potential to improve patient outcomes, reduce revision surgeries, and enhance comfort in both orthopedic and dental medicin